Role of zinc in chronic telogen effluvium in serum and hair of patients with alopecia - Shayan Zufishan,; Zeba Haque,; Shazia Nazar,; Erum Afaq,; Erum Aamir,; Sara Rafique, (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the levels of zinc in hair and serum samples of chronic telogen effluvium patients. Method: The case-control study was conducted at the Dow University of Health Sciences, Karachi, from April 2017 to May 2018, and comprised diagnosed cases of chronic telogen effluvium in group A, and healthy controls matched for age and gender in group B. Hair pull test was done, and level of zinc in hair and serum samples was determined using atomic absorption spectrophotometer. Data was analysed using SPSS 21. Results: Of the 100 subjects, 50(50%) were in group A; 28(56%) females ad 22(44%) males with mean age 27.46±4.98 years. There were 50(50%) subejcts in group B; 26(52%) males ad 24(48%) females with mean age 28.34±4.92 years (p>0.05). Significantly low levels of zinc were observed in serum as well as hair samples in group A compared to group B (p<0.05). A positive significant association was observed in the level of zinc in hair with their concentration in the serum of subjects in both the groups (r=0.310, p<0.05). Conclusion: Low levels of zinc in hair and serum were found to be associated with chronic telogen effluvium. Key Words: Chronic telogen effluvium, Zinc, Alopecia, Hair loss